2018
DOI: 10.1016/j.bja.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Degree of obesity is not associated with more than one intubation attempt: a large centre experience

Abstract: Increasing BMI was associated with increasing odds of difficult intubation in the lean range. At higher BMI, the odds of difficult intubation remain elevated, but there is no additional increase in odds with further increase in BMI. Obese patients were thus harder to intubate than lean ones, but difficult intubation was no more likely in morbidly obese patients than in those who were only slightly obese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 30 publications
4
29
0
3
Order By: Relevance
“…A signi cantly greater proportion of di cult laryngoscopy and tracheal intubation had been found in obese patients [11,12]. However, in our study, we found there was no signi cant difference between the easy and di cult groups (25.1±3.3 vs 25.7±2.5, P=0.261) which was in accordance with the study reported by Prakash et al [13].…”
Section: Discussionsupporting
confidence: 91%
“…A signi cantly greater proportion of di cult laryngoscopy and tracheal intubation had been found in obese patients [11,12]. However, in our study, we found there was no signi cant difference between the easy and di cult groups (25.1±3.3 vs 25.7±2.5, P=0.261) which was in accordance with the study reported by Prakash et al [13].…”
Section: Discussionsupporting
confidence: 91%
“…The majority of these scenarios arise due to poor visualization of laryngeal inlet -"epiglottis only view" ostensibly due to condition such as pharyngeal obstruction, obesity, limited cervical mobility etc. [5][6][7]. Situations in which glottic view is expected to improve by external laryngeal manipulationa readily available airway adjunct device (commonly known as bougie) is recommended to assist tracheal intubation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Today, obesity is a major public health and policy problem in many countries because of its prevalence, costs, and adverse health effects. 4 In this edition of the British Journal of Anaesthesia, Saasouh and colleagues 5 address the question of whether obesity or a high BMI is associated with difficult tracheal intubation. The authors used a retrospective database approach and electronic data sets of 67 702 adult patients having elective, non-cardiac surgery and requiring tracheal intubation at the Cleveland Clinic in the USA.…”
mentioning
confidence: 99%
“…Factors to improve tracheal intubation success 11 dif difficultdremain largely unknown in the study of Saasouh and colleagues. 5 As different parameters were used with a retrospective approach, it remains unclear which factors affect difficulty of intubation.…”
mentioning
confidence: 99%
See 1 more Smart Citation